Endoscopic ultrasound-guided tissue sampling of small subepithelial tumors of the upper gastrointestinal tract with a 22-gauge core biopsy needle - Schlag, Christoph; Menzel, Christoph; Götzberger, Manuela; Nennstiel, Simon; Klare, Peter; Wagenpfeil, Stefan; Schmid, Roland M.; Weirich, Gregor; von Delius, Stefan (Endoscopy International Open, 2017)
Background and study aims The optimal approach to small subepithelial tumors (SETs) of the upper gastrointestinal tract remains inconclusive. The aim of this study was to evaluate endoscopic ultrasound-guided fine needle biopsy (EUS-FNB) for less invasive tissue sampling of small SETs of the upper gastrointestinal tract.Patients and methods In this prospective observational study patients with small ( ≤ 3 cm) SETs of the upper gastrointestinal tract were eligible and underwent EUS-FNB with a 22-gauge core biopsy needle. The main outcome measure was the diagnostic yield. The number of obtained core biopsies was also assessed.Results Twenty patients were included. The mean SET size was 16 mm (range 10 – 27 mm). EUS-FNB was technically feasible in all cases and no complications were observed. The diagnostic yield was 75 %. Core biopsy specimens were obtained in only 25 % of cases.Conclusion EUS-FNB with a 22-gauge core biopsy needle of small SETs can achieve a definite diagnosis in the majority of cases. However, because core samples cannot regularly be obtained, EUS-FNB seems not to be convincingly superior to standard EUS-FNA in this setting